2014
DOI: 10.1186/1471-2164-15-292
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of genetic variation, epigenetic regulation, and the transcriptome to elucidate the biology of platinum sensitivity

Abstract: BackgroundUsing genome-wide genetic, gene expression, and microRNA expression (miRNA) data, we developed an integrative approach to investigate the genetic and epigenetic basis of chemotherapeutic sensitivity.ResultsThrough a sequential multi-stage framework, we identified genes and miRNAs whose expression correlated with platinum sensitivity, mapped these to genomic loci as quantitative trait loci (QTLs), and evaluated the associations between these QTLs and platinum sensitivity. A permutation analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Further integration of global gene expression data, miRNA and SNPs into quantitative trait loci (QTLs) allowed for identification of functional links, e.g. between particular SNPs (rs11138019), expression of miRNA (miR30a), activity of membrane efflux transporters (ABCD2) and cisplatin sensitivity in ovarian cancer (LaCroix et al, 2014). Recent global studies focused on other metal-based cytotoxic drugs, e.g.…”
Section: Heptaplatinmentioning
confidence: 99%
“…Further integration of global gene expression data, miRNA and SNPs into quantitative trait loci (QTLs) allowed for identification of functional links, e.g. between particular SNPs (rs11138019), expression of miRNA (miR30a), activity of membrane efflux transporters (ABCD2) and cisplatin sensitivity in ovarian cancer (LaCroix et al, 2014). Recent global studies focused on other metal-based cytotoxic drugs, e.g.…”
Section: Heptaplatinmentioning
confidence: 99%
“…Mitra et al reported that another FKBP5 intronic SNP, rs3798346, was significantly associated with event-free survival and overall survival in pediatric acute myeloid leukemia (AML) patients treated with cytarabine [56]. This is one among many examples for which our group and others have used LCLs to characterize biomarkers at both functional and mechanistic levels [1012,1416,18,19,2124]. …”
Section: Ebv-transformed Lymphoblastoid Cell Line Modelsmentioning
confidence: 99%
“…Recently additional information for less common and rare variants has been generated by the 1000 Genome Project using Next-Generation Sequencing [42]. This model has also been extensively characterized at the molecular level, including DNA CNV, DNA methylation, mRNA and miRNA expression, protein expression as well as cytotoxicity data for various anticancer drugs [37,12,2022,2426,59]. These data have also been used to develop statistical methodology related to the integrated analysis of different omic data to help identify pharmacogenomic biomarkers [6,12].…”
Section: Ebv-transformed Lymphoblastoid Cell Line Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis for cisplatin, one 1 SNP associated with the expression of 1 miRNA and 1 gene was found (rs11138019 genotype, miR-30d expression, and ABCD2 expression), and functional characterization of this association was confirmed in the SKOV3 ovarian cancer cell line [80]. They then integrated transcriptional gene expression and miRNA expression with their known single nucleotide polymorphism (SNP) genotypes to identify robust SNP associations with the IC 50 .…”
Section: Mirnas Associated With Cisplatin Resistance/sensitivitymentioning
confidence: 99%